Reduction in colposcopy workload and associated clinical activity following human papillomavirus (HPV) catch‐up vaccination programme in Scotland: an ecological study. (9th March 2017) - Cruickshank, ME; Pan, J; Cotton, SC; Kavanagh, K; Robertson, C; Cuschieri, K; Cubie, H; Palmer, T; Pollock, KG
Abstract : Objective: To measure patterns of clinical activity at colposcopy before and after vaccinated women entered the Scottish Cervical Screening Programme (SCSP). Design: Population‐based observational study using nationally collected data. Setting: Scottish colposcopy clinics. Sample: All women with a date of birth on or after 1 January 1985 who attended colposcopy in Scotland between 2008 and 2014. Methods: Routinely collected data from the Scottish National Colposcopy Clinical Information Audit System (NCCIAS) were extracted, including: referral criteria, referral cervical cytology, colposcopic findings, clinical procedures, and histology results. Analysis was restricted to those referred to colposcopy at age 20 or 21 years. Main outcome measures: Referral criteria, positive predictive value of colposcopy, default rates, and rates of cervical biopsies and treatments. Results: A total of 7372 women referred for colposcopy at age 20 or 21 years were identified. There was a downward trend in the proportion of those referred with abnormal cytology (2008/9, 91.0%; 2013/14, 90.3%; linear trend P = 0.03). Women were less likely to have diagnostic or therapeutic interventions. The proportion with no biopsy (2008/9, 19.5%; 2013/14, 26.9%; linear trend P < 0.0001) and no treatment (2008/9, 74.9%; 2013/14, 91.8%; linear trend P < 0.0001) increased over the period of observation. Conclusions: A reduction in clinical activity related to abnormal screening referrals is likely to be associated with the human papillomavirus (HPV) catch‐up immunisation programme. Referral criteria and the service provision of colposcopy needs to be planned carefully, taking account of the increasing number of women who have been immunised against HPV that will be entering cervical screening programmes worldwide. Tweetable abstract: Colposcopy referral criteria and service planning need attention following HPV immunisation programme. Tweetable abstract: Colposcopy referral criteria and service planning need attention following HPV immunisation programme.